2000
DOI: 10.1084/jem.191.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Vα14 Nkt Cell–Mediated Cytotoxicity by Interleukin 4 in an Autocrine Mechanism Resulting in the Development of Concanavalin a–Induced Hepatitis

Abstract: The administration of concanavalin A (Con A) induces a rapid severe injury of hepatocytes in mice. Although the Con A–induced hepatitis is considered to be an experimental model of human autoimmune hepatitis, the precise cellular and molecular mechanisms that induce hepatocyte injury remain unclear. Here, we demonstrate that Vα14 NKT cells are required and sufficient for induction of this hepatitis. Moreover, interleukin (IL)-4 produced by Con A–activated Vα14 NKT cells is found to play a crucial role in disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
431
7
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(462 citation statements)
references
References 56 publications
23
431
7
1
Order By: Relevance
“…ConA has been extensively used in the model of autoimmune hepatitis and CD4 + T cells as well as NKT cells were suggested to play a role in this model (Kaneko et al 2000;Tiegs et al 1992;Toyabe et al 1997;Yang et al 2010). In addition, ConA has been reported to show anti-tumor effects, which are mediated by the intrahepatic activation of both NK cells (Miyagi et al 2004) and CD8 + T cells (Chang et al 2007;Lei and Chang 2009).…”
Section: Discussionmentioning
confidence: 99%
“…ConA has been extensively used in the model of autoimmune hepatitis and CD4 + T cells as well as NKT cells were suggested to play a role in this model (Kaneko et al 2000;Tiegs et al 1992;Toyabe et al 1997;Yang et al 2010). In addition, ConA has been reported to show anti-tumor effects, which are mediated by the intrahepatic activation of both NK cells (Miyagi et al 2004) and CD8 + T cells (Chang et al 2007;Lei and Chang 2009).…”
Section: Discussionmentioning
confidence: 99%
“…V␣14 ϩ NKT have been implicated in a number of immunemediated pathologies including graft-vs-host disease, autoimmune hepatitis, and in fetal loss (17)(18)(19). In addition, a disease-controlling role for NKT cells has been shown in V␣14-J␣18 transgenic (Tg) 5 nonobese diabetic mice (20).…”
Section: Invariant V␣14 ؉ Nkt Cells Participate In the Early Responsementioning
confidence: 99%
“…Following Con A administration, liver histology shows massive granulocyte accumulation, CD4 ϩ T cell infiltration, and hepatocyte necrosis/apoptosis (3,4). The induction of this hepatitis depends on CD1d-restricted invariant NKT cells, that express an invariant V␣14J␣18 TCR (5,6). Thus, J␣18 Ϫ/Ϫ and CD1d Ϫ/Ϫ mice that lack NKT cells are resistant to Con A-induced hepatic injury (5,6), whereas the adoptive transfer of NKT cells isolated from wild-type (WT) 3 mice into healthy CD1d Ϫ/Ϫ or J␣18 Ϫ/Ϫ mice restores hepatic injury mediated by Con A.…”
mentioning
confidence: 99%
“…The induction of this hepatitis depends on CD1d-restricted invariant NKT cells, that express an invariant V␣14J␣18 TCR (5,6). Thus, J␣18 Ϫ/Ϫ and CD1d Ϫ/Ϫ mice that lack NKT cells are resistant to Con A-induced hepatic injury (5,6), whereas the adoptive transfer of NKT cells isolated from wild-type (WT) 3 mice into healthy CD1d Ϫ/Ϫ or J␣18 Ϫ/Ϫ mice restores hepatic injury mediated by Con A. Previous studies have shown that Con A activates hepatic resident NKT cells to produce IL-4 (5, 6); IL-4, in turn, acts on NKT cells in an autocrine fashion to induce Fas ligand (FasL) expression on these cells, which subsequently promotes hepatocyte cell death (i.e., cytotoxicity), possibly by interacting with Fas-expressing hepatocytes.…”
mentioning
confidence: 99%